H2S as a new component in stomatal signaling during pathogen attack - Scuffi, Denise (2020)
Hydrogen sulfide (H2S) is a new gasotransmitter involved in several processes in plants. It is endogenously produced in part, by the cytosolic enzyme L-cysteine desulfhydrase 1 (DES1) which degrades L-cysteine into H2S, piruvate and ammonia. It is known that participates actively during stomatal closure induced by different stimuli. Stomata are pores surrounded by a pair of cells, guard cells, through which plants regulate the gaseous exchange with the environment and the loss of water by evapotranspiration. Its regulation is important to maintain carbon and water homeostasis and also for plant defense since pathogen can enter into the plant through them.In our lab we demonstrated, using Arabidopsis thaliana epidermal peels, that H2S and DES1 participate in bacterial elicitor flg22-induced stomatal closure. This signaling network includes other components like NADPH oxidase RBOHD and phosholipase C2 (PLC2).Here we move forward studying the role of H2S during flg22-induced stomatal closure. We made use of wild type Arabidopsis plants to evaluate pathogen-response genes expression specifically in guard cells upon GYY (a H2S donor) treatments and DES1 expression under flg22 treatment. Furthermore we analyzed MAPK activity in response to flg22 and Pst DC3000 hrcC- infection in Arabidopsis des1 mutant plants.